A systematic study on complementary metal-oxide semiconductor technology (CMOS) and Internet of Things (IOT) for radioactive leakage detection in nuclear plant - Swayam Patel; Sakshi Sutaria; Rajveer Daga; Manan Shah; Mitul Prajapati (Nuclear Analysis)
Although nuclear power plants produce about 20% of India's power, the risk posed by radioactive leakage is considerable. Radiation leakage detection devices must be installed in all nuclear power plants to ensure that avoidable catastrophes never occur again and that the loss of human life is prevented. A safe atmosphere for inhabitants and workers may be ensured by keeping a consistent radiation level in all applications that use radioactive material. Complementary Metal-Oxide Semiconductor technology, or CMOS, uses complementary and symmetrical MOSFETS for logic-based functions in various applications, such as analog circuits (CMOS sensors). The Internet of Things (IoT) extends the power of the Internet beyond computing devices to a multitude of other things, processes, and environments. The main objective of this paper is to find a better and more creative solution for radioactive leakage detection techniques over present-day techniques. In this paper, the Authors aim to integrate CMOS and IOT applications for radioactive leakage detection methods on an industrial level. Within this paper, we have given brief descriptions of CMOS and IoT with their types, functions, methodology, and applications. CMOS is considered to be the most sophisticated and precise technology that can be employed to measure radiation leaks of all types (alpha rays, beta rays, gamma rays, and neutrons). With the help of IOT, massive disasters can be averted using complex alert systems. A well-coordinated combination of the two technologies has the potential to vastly increase leak detection potential and consistency. The study's major goal is to develop new and improved technology for detecting released radiation in the industry in order to obtain real-time information about the material leaked, as well as the location of the leak and the quantity of leakage that occurred, in order to reduce the danger of a natural catastrophe.